Fluorogenic DNA-PAINT for faster, low-background super-resolution imaging - Chung, Kenny K. H.; Zhang, Zhao; Kidd, Phylicia; Zhang, Yongdeng; Williams, Nathan D.; Rollins, Bennett; Yang, Yang; Lin, Chenxiang; Baddeley, David; Bewersdorf, Joerg (Nature methods, 2022)
DNA-based points accumulation for imaging in nanoscale topography (DNA-PAINT) is a powerful super-resolution microscopy method that can acquire high-fidelity images at nanometer resolution. It suffers, however, from high background and slow imaging speed, both of which can be attributed to the presence of unbound fluorophores in solution. Here we present two-color fluorogenic DNA-PAINT, which uses improved imager probe and docking strand designs to solve these problems. These self-quenching single-stranded DNA probes are conjugated with a fluorophore and quencher at the terminals, which permits an increase in fluorescence by up to 57-fold upon binding and unquenching. In addition, the engineering of base pair mismatches between the fluorogenic imager probes and docking strands allowed us to achieve both high fluorogenicity and the fast binding kinetics required for fast imaging. We demonstrate a 26-fold increase in imaging speed over regular DNA-PAINT and show that our new implementation enables three-dimensional super-resolution DNA-PAINT imaging without optical sectioning. Two-color fluorogenic DNA-PAINT introduces self-quenching, kinetics-optimized probe designs. This approach improves imaging speed 26-fold and eliminates the need for optical sectioning.